A STUDY OF NEEDS: VIRTUAL REALITY-BASED MODEL IN FOSTERING THE NATIONALISM CHARACTER IN PRIMARY SCHOOL - Freddy Widya Ariesta; Bunyamin Maftuh; Sapriya Sapriya; Ernawulan Syaodih (Universitas Majalengka, 2023)
In today's digital era, education faces challenges and opportunities to integrate technology in the learning process to provide a deeper and more meaningful experience for students. With this background, this study was conducted to investigate the level of nationalism of elementary school students and evaluate the potential and need for learning models based on Virtual Reality (VR). This research involved the participation of 203 students and 12 teachers from grades 4 to 6 in 10 elementary schools located in West Jakarta. Through a specially designed questionnaire, data is collected and then analyzed using quantitative methods. The results of the analysis show that only 48.7% of students show strong characteristics of nationalism, while the other 51.3% appear to lack these characteristics. Apart from that, from the educator side, as many as 84.7% of teachers expressed support and an urgent need for the adoption of VR-based learning models. Based on these findings, this research recommends the development and implementation of a VR-based learning model which aims to increase understanding and appreciation of nationalist values among students. It is hoped that through the integration of educational content with VR technology, students can experience a more immersive, interesting, and effective learning experience in building a sense of nationalism. Di era pendidikan saat ini, paradigma pembelajaran membutuhkan model yang menggabungkan teknologi untuk menciptakan kesempatan belajar yang signifikan bagi siswa. Tujuan dari penelitian ini adalah untuk mengidentifikasi sejauh mana sifat-sifat nasionalis yang ditunjukkan oleh siswa sekolah dasar dan mengevaluasi perlunya model pembelajaran berdasarkan realitas virtual. Penelitian ini menggunakan pendekatan kualitatif, dengan melibatkan sampel 203 siswa dan 12 guru dari kelas 4-6 di sebuah sekolah dasar di Jakarta Barat. Penggunaan kuesioner sebagai alat pengumpulan data. Data yang diperoleh dianalisis secara kualitatif, dengan menyajikan hasil dalam bentuk deskriptif persentase. Temuan dari penelitian ini mengungkapkan bahwa tingkat nasionalisme di kalangan siswa sekolah dasar kelas 4-6 relatif rendah, sebagaimana dibuktikan oleh tanggapan dari 203 partisipan. Data menunjukkan bahwa hanya 48,7% dari partisipan yang mempunyai karakter nasionalisme, sementara 51,3% sisanya yang terdiri dari 104 siswa belum memiliki karakter nasionalisme. Sehingga berdasarkan studi pendahuluan terkait dengan analisis kebutuhan penelitian tentang perlunya model pembelajaran berbasis virtual reality, sebagian besar guru di sekolah dasar, yaitu sekitar 84,7%, menyatakan perlunya model pembelajaran tersebut. Penelitian ini mengusulkan model pembelajaran berbasis virtual reality yang bertujuan untuk meningkatkan pengalaman belajar siswa melalui integrasi konten media virtual reality yang beragam, menarik dan memberikan pengalaman imersif. Tujuan akhirnya adalah untuk membangun rasa nasionalisme siswa di sekolah.